TOPONIMI DESA-DESA DI KECAMATAN SINGOSARI KABUPATEN MALANG - Muhammad Edy Thoyib (JP : JURNAL PENDIDIKAN, 2021)
Abstract: The present study aims to investigate the toponymy of 17 villages in Singosari Subdistrict, Malang Regency, focusing on linguistic aspects and the back-ground of villages’ naming. This study applies a quali-tative descriptive approach.  The data were collected from the official website of Malang government and by interviewing the informants. The data were analyzed using morphosemantics to find out the meaning and the word-formation of the villages’ names. To inquire the background of the naming, the data were then analyzed using Sudaryat’s toponymy theory. The results of the study revealed that the villlages’ names are composed of monomorphemic words, an affixed polymorphemic, and compound poly-morphemics. In terms of the toponymy category, the names of villages in Singosari District have naming backgrounds based on 1) the em-bodiment aspects of water, earth, natural objects, and natural environment; 2) social aspects in the form of community expec-tations, community activities, and community struggles; and 3) cultural aspects in the form of folklore, namely place legends and myths.Keywords: toponymy, toponomastics, folklo